PERFORMANCE ASSESSMENT SYSTEM NEEDS ANALYSIS OF LP3I BUSINESS COLLEGE LECTURER BANDA ACEH USING The METHOD Of VIEWPOINT ORIENTED REQUIREMENT DEFINITION (VORD) - Wibawa, Muhammad Bayu (Ubudiyah Indonesia University, 2016)
ABSTRAKThe needs of the software must be started from the parties involved in thedevelopment of a system to be built. The statement describes the needs ofconsumers or users of the system, nor the clien stokeholder though. Inorder to get the system needs to do some activity or activities include:requirement elicitation requirment, analysis and negotiation, requirementdocumentation, validation requirement. This activity aims to produce adocument called document specification. Of some sort of method toanalyze the needs of the system, one of the methods that can be appliedon requirement engineering is the method of Viewpoint OrientedRequirements Definition (VORD). VORD method is one method used todefine needs with an approach viewpoint (point of view) the users of thesystem. The results of the analysis of the VORD method this will generaterequirement specification with the help of a tool i.e. VORD tool. The resultsof this analysis in the form of a document that describes the system needsto be built.Keywords: Requirement Engineering, VORD Method